Synthetic surgical meshes used in abdominal wall surgery: Part II—Biomechanical aspects. Issue 4 (21st December 2015) - Todros, S.; Pavan, P.G.; Pachera, P.; Natali, A.N.
Abstract: This work reports the second part of a review on synthetic surgical meshes used for abdominal hernia repair. While material and structural characteristics, together with mesh–tissue interaction, were considered in a previous article (Part I), biomechanical behavior is described here in more detail. The role of the prosthesis is to strengthen the impaired abdominal wall, mimicking autologous tissue without reducing its compliance. Consequently, mesh mechanical properties play a crucial role in a successful surgical repair. The main available techniques for mechanical testing, such as uniaxial and biaxial tensile testing, ball burst, suture retention strength, and tear resistance testing, are described in depth. Among these methods, the biaxial tensile test is the one that can more faithfully reproduce the physiological loading condition. An outline of the most significant results documented in the literature is reported, showing the variety of data on mesh mechanical properties. Synthetic surgical meshes generally follow a non‐linear stress–strain behavior, with mechanical characteristics dependant on test direction due to mesh anisotropy. Ex‐vivo tests revealed an increased stiffness in mesh explants due to the gradual ingrowth of the host tissue after implant. In general, the absence of standardization in test methods and terminology makes it difficult to compare results from different studies. Numerical models of the abdominal wall interacting with surgical meshes were also discussed representing a potential tool for the selection of suitable prostheses. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 892–903, 2017.